Agricultural transformation and ecosystem services: A case study from Shaanxi Province, China. (November 2017) - Song, Bingjie; Robinson, Guy M.; Zhou, Zhongxue
Abstract: This paper analyses changes to ecosystem services (ESS) over the past thirty years in a small part of the hinterland of Xi'an, a city of nearly nine million population in Shaanxi Province, China. Using field survey and interviews with local farmers, the study provides micro-scale exemplification of the transformation occurring around major urban growth centres in China in response both to urbanization and agricultural modernization. The effects of urban growth upon agriculture are illustrated by wholesale changes in the type of production, increasing the value of provisioning services by replacing traditional cereals cultivation with fruit, which reflects the impact of the dynamic urban market. Five different types of ESS are calculated and analyzed, taking into consideration changing land management practices associated with the principal new crops in the study area, cherries and grapes. The widespread adoption of cherries as the main cash crop has also afforded farmers an additional source of revenue from tourists visiting the area to see the Spring-time blossom, pick the fruit and obtain a 'rural experience' by interacting with farmers and eating local food. The increased wealth for farm households has prevented the 'hollowing' of villages close to the expanding metropolitan area, but longer distance commuting to work in the city is now common for younger rural residents. Detailed calculation of the changing pattern of EES reveals the significant effects not only of the introduction of new crops but also the role of particular land management practices. Further analysis of these practices is proposed to obtain better understanding of the balance between positive and negative changes to EES. Highlights: Ecosystem services are calculated for a village close to a major Chinese city. Agricultural transformation reflects impacts of the nearby urban market. The value of provisioning services rose sevenfold in thirty years. Local farming practices have both positive and negative effects on ecosystems. Rural tourism offers new income streams for local households.